Intentional or incidental? Learning through play according to Australian educators' perspectives. Issue 2 (15th March 2022) - Colliver, Yeshe
ABSTRACT: Recent early childhood education and care (ECEC) reforms across the globe are placing greater emphasis on the intentionality of educators' pedagogy. In Australia, a National Quality Agenda (NQA) has significantly reformed ECEC through the country's first national learning framework, which demands educators take a more intentional (active) role in teaching a play-based curriculum. Because educators' capacity to confront these challenges will be reflected in their perspectives, a case study of educators' perspectives on learning through play was conducted shortly after the new framework's introduction to the field. A cultural-historical framing provided a contextualised, deductive analysis of educators' practices and values. Findings indicated educators believe children's learning from their play was associated with educators' passive rather than active practices. Rather than intentional, it seemed to be merely coincidental that child-chosen play resulted in learning of curriculum content. Consistent with other countries where educators appear torn between curricular demands for adult-driven outcomes and a pedagogy of play, findings indicate educators were adept at justifying child-determined learning in relation to adult-determined curricular demands. However, the findings pinpoint exactly where and how educators lacked support to actively engage with and extend child-initiated play for learning.